Analisis Strategi Penerapan dan Dampak Permainan Judi Online di Kalangan Masyarakat - Billah, Nanda Putra; Imelia Febrianti; Suci Dwi Noviarum; Vrisco Putra Vachruddin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
Online gambling games have become an increasingly widespread phenomenon among teenagers and have significant social, economic and psychological impacts. This research aims to analyze implementation strategies and the impact of online gambling games among teenagers while providing insight into the risks associated with these activities. This research uses a literature review method, which is a structured approach to collecting, assessing, and integrating research relevant to this topic. Data is taken from literature such as articles, books and others. It is hoped that this research can contribute to efforts to prevent the negative impacts of online gambling through implementing policies, educational programs and increasing awareness among the public.